2018
DOI: 10.21767/1791-809x.1000549
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antimicrobial Resistance Pattern of Staphylococci Isolated From Cottage Cheese (Ayib) and Yoghurt (Ergo) in Selected Districts of Jimma Zone, Ethiopia

Abstract: Background: Staphylococci related illness is among serious public-health problems and the second most expensive diseases to treat in developing country. According to WHO estimation, staphylococcal related food borne disease are the second most common food borne disease next to salmonella. Although staphylococci related illness is affecting the majority of Ethiopian, much is not known about the extents of Staphylococcus species and their antimicrobial resistance pattern in cottage cheese (Ayib) and yoghurt (Erg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
6
8
2
Order By: Relevance
“…Regarding contamination of yogurt samples with CoNS; Argaw et al [36] detected a lower incidence of the organism (2%), and on contrary to this study, Onen and Aygun [37] could not isolate CoNS from yogurt samples.…”
Section: Discussioncontrasting
confidence: 98%
“…Regarding contamination of yogurt samples with CoNS; Argaw et al [36] detected a lower incidence of the organism (2%), and on contrary to this study, Onen and Aygun [37] could not isolate CoNS from yogurt samples.…”
Section: Discussioncontrasting
confidence: 98%
“…Another study conducted in Jimma, Ethiopia, demonstrated a higher prevalence of S. aureus (52%) in bovine milk [ 22 ]. A study in selected regions of Jimma showed 14.3% prevalence of S. aureus in cottage cheese and yogurt which is in agreement with the 11.3% findings of the current study [ 15 ]. A potenital reason why the prevalence of S. aureus in the current study was low compared to the previous study, could be due to the fact that dairy farmers, and milk and other dairy product handlers in the Addis Ababa, are in a better position regarding awareness of hygienic practices.…”
Section: Discussionsupporting
confidence: 92%
“…A crosssectional study was conducted from December 2019 to May 2020 to investigate the occurrence and antimicrobial susceptibility of S. aureus in milk and dairy products. Sample size was determined using the formula described previously [13] with 95% confidence, desired absolute precision of 5% and an expected 12.6% prevalence of S. aureus in raw milk from previous study [14] and 5% in dairy products (yogurt "Ergo" and cottage cheese "Ayib") [15]. This resulted in minimum sample size of 169 for raw cow milk and 73 for other dairy products.…”
Section: Study Design and Sample Size Determinationmentioning
confidence: 99%
“…However, in disagreement with the current study where there was no growth indicated in yoghurt samples their results showed that 5 samples of yoghurt out of 30 samples 16%, were contaminated with CNS. Also, [30] detected that out of 200 sample of cottage cheese only (44 samples 22%) were contaminated with staphylococci which is lower than the amount of staphylococci contamination in our study (34.9%), and biochemical results found that (19 samples; 9.5%) were contaminated with CNS. But in disagreement with current study where no staphylococcal growth was indicated in yoghurt samples their results showed out of 200 yoghurt samples (13 samples; 6.5%) were contaminated with staphylococci and biochemical characterization results showed that only (4 samples; 2%) were contaminated with CNS.…”
Section: Enumeration Of Bacterial Numberscontrasting
confidence: 70%